الريف البرازيلي أنموذجا للتنمية في سياق الاقتصاد الأخضر بعد عام 2003( ) تأليف: لورو ماتي (lark, 2019)
ABSTRACT:This paper discusses the Brazilian rural development model in the context of Green Economy and the sustainable development debate, issues that have be discussed in international sphere. this paper will try to answer the following question: Is the green economy approach a good way to promote sustainable development in countries like Brazil? To answer this question we are concentrating our analysis in the agricultural sector. we analyzed the Brazilian rural development model and the public investment in the agricultural and livestock sector, seeking to emphasize the government option towards primary commodity production for international markets. The main conclusions of the paper is that to understand the Brazilian society today we need to take account a transition from an agrarian society to an industrial society, a process that occurred in Brazil during the 20th Century. This path Brazilian society has mapped since its inception is marked by the contradiction between abundance for a few portions of the population and famine for the great majority.  if the year 2011 showed Brazil to be the 6th largest economy in the world, at the same time the world and the greatest rates of social exclusion.
Keywords: Brazil; sustainable development; Brazilian rural; Brazil Economy; Green Economy